2012
DOI: 10.1364/ol.37.002955
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional photoprecipitation of oriented LiNbO_3-like crystals in silica-based glass with femtosecond laser irradiation

Abstract: We demonstrate crystals (LiNbO(3)-like) that were space-selectively nucleated and grown in the bulk of silica-based glass by femtosecond laser irradiation at a high repetition rate (typ. 300 kHz). Oriented crystals with their polar axis mostly aligned with or perpendicular to the laser scanning direction have been fabricated by manipulation of the temperature gradient in adjusting the laser parameters. The mechanism for the orientation of femtosecond laser-induced crystallization is briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…The process yields single-crystal architecture in glass (SCAG) comprising of straight and curved lines. A continuous wave (CW) laser of suitable wavelength is used to create SCAG at or near the surface 1, 4-7 , whereas femtosecond (fs) laser can yield SCAG in 3D deep inside the glass 2,3 . In either case, the glass generally melts at the focal point of the laser and crystal forms as the melt solidifies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process yields single-crystal architecture in glass (SCAG) comprising of straight and curved lines. A continuous wave (CW) laser of suitable wavelength is used to create SCAG at or near the surface 1, 4-7 , whereas femtosecond (fs) laser can yield SCAG in 3D deep inside the glass 2,3 . In either case, the glass generally melts at the focal point of the laser and crystal forms as the melt solidifies.…”
Section: Introductionmentioning
confidence: 99%
“…It fabricated 'highly oriented' 2D crystal patterns of LiNbO 3 , β-BaB 2 O 4 , and β'-Gd 2 (MoO 4 ) 3 , within intrinsically simple silicate or borate glass matrix, where laser induced crystal growth occurs from the melt. The 2D patterns were created as array of lines with a small step between them.…”
Section: Introductionmentioning
confidence: 99%
“…However, the spatial distribution of these properties is difficult to control by conventional glass production methods (i.e., melt-quenching and sol-gel). One candidate technique for local modification of glass properties is laser processing [2][3][4][5][6][7][8][9][10][11]. In particular, femtosecond (fs) laser processing has been investigated as a powerful technique to modify the properties of glass three dimensionally [3][4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%
“…One candidate technique for local modification of glass properties is laser processing [2][3][4][5][6][7][8][9][10][11]. In particular, femtosecond (fs) laser processing has been investigated as a powerful technique to modify the properties of glass three dimensionally [3][4][5][6][7][8][9][10][11]. Recently, several researchers found that irradiation of glass with focused fs laser pulses at high repetition rate (100 kHz-1 MHz) induces local melting around the focal region, and the elemental distribution changes in the molten region [5][6][7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%
See 1 more Smart Citation